Physico-chemical and sensory characterization of two rice (Oryza sativa) varieties during aging process - Araya-Morice, Adriana; Mora-Norori, Ana Laura; Cubero-Castillo, Elba; Azofeifa, Alvaro; Araya-Quesada, Yorleny (Agronomía Mesoamericana, 2022)
Introduction. Once harvested, paddy rice is stored in aerated silos for temperature control, which is known as rice aging. During aging, physicochemical, and physiological changes occur in the rice grain, these changes affect its culinary quality. Objective. To determine the effect of aging time on the physicochemical and sensory characteristics of two rice varieties. Materials and methods. This study was carried out in Agrifood Science Faculty Laboratories of the Universidad de Costa Rica, between September 2018 and March 2019. The two rice varieties studied were grown in Osa, Puntarenas. The first cv. Lazarroz FL, indica type, and the second cv. UCR-168-10, aromatic type were stored for 4.5 months. During storage, total starch, resistant starch, amylose, moisture, protein, was determined, and sensory attributes were evaluated with a trained sensory panel. Results. The two rice varieties studied don’t show significant differences during 4.5 months of storage in moisture, total starch, and resistant starch. Amylose content showed variation without a clear trend. Protein content was reduced during aging until 2,5 months of storage. According to the sensory test, attributes such as integral flavor and stickiness did not show significant differences throughout the study, while the remaining parameters did, either over time or between varieties. Cooked rice appearance showed an improvement up to 2,5 months aging for the two varieties. Whiteness of rice increased for both varieties during aging. Conclusion. Storing rice for 2,5 months achieved the desired changes in protein and sensory attributes for the rice varieties evaluated.